Coopetition typology revisited – a behavioural approach. (1st January 2014) - Czakon, Wojciech; Rogalski, Mariusz
Coopetition strategies have been recognised as complex and dynamic inter-organisational phenomena. Yet, the heterogeneity of coopetition has very seldom been empirically investigated. Our study contributes to fill this gap by exploring coopetition strategies adopted on the polish energy market. We test the relationship-intensity-based coopetition typology with behavioural variables. The serial case study conducted on 20 firms unveils coopetition as the juxtaposition of competition and collaboration in active and passive forms, yielding nine instead of four theoretically possible coopetition types. Our results also suggest that mandated coopetition displays moderate or weak levels, while resource-driven coopetition is active.